Responses of isolated balsam-fir stem segments to exogenous ACC, IAA, and IBA - Rodney Arthur Savidge (Forestry Research)
In this investigation, the effects of exogenous indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), and 1-aminocyclopropane-1-carboxylic acid (ACC) on anatomical development within cultured segments of Abies balsamea (L.) Mill. were compared, using debudded and defoliated leaders produced in the preceding year as bioassay material. In stem apical regions, IAA promoted radial enlargement of pre-existing cortical resin ducts and attending parenchyma enlargement, whereas IBA promoted cell division and expansion of parenchyma on the outer edge of phloem without altering cortical duct shape. Cortical woody ducts, each partially surrounded by cambium, were observed as a novel but infrequent feature. A single cortical woody duct was spatially associated with each mature leaf as its vascular trace, and they were not encountered elsewhere in the cortex, nor were they induced to form in response to any hormone application. An unknown leaf factor induces the development of cortical woody ducts. Both IAA and IBA promoted cell division in the vascular cambium. The common cellular response at the interface between the latewood boundary and cambial zone was the radial expansion of primary-walled fusiform cambial cell derivatives with little if any ensuing tracheary element (TE) differentiation. Enhanced TE production at basal stem positions occurred when ACC was provided with IAA and/or IBA, and an IAA + IBA + ACC combination produced a basal stem response similar to that in untreated segments having intact leaves. The data support the conclusion that IAA, IBA, and ACC have distinct but complementary roles in the overall regulation of the types of cellular differentiation that contribute to cortex histogenesis and diameter growth of balsam-fir leaders.